2020
DOI: 10.1038/s41598-020-59462-w
|View full text |Cite
|
Sign up to set email alerts
|

Matrix protease production, epithelial-to-mesenchymal transition marker expression and invasion of glioblastoma cells in response to osmotic or hydrostatic pressure

Abstract: Both hydrostatic and osmotic pressures are altered in the tumour microenvironment. Glioblastoma (GBM) is a brain tumour with high invasiveness and poor prognosis. We hypothesized that physical and osmotic forces regulate glioblastoma (GBM) invasiveness. the osmotic pressure of GBM cell culture medium was adjusted using sodium chloride or water. Alternatively, cells were subjected to increased hydrostatic force. The proteolytic profile and epithelial-mesenchymal transition (EMT) were investigated using zymograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 47 publications
0
18
0
Order By: Relevance
“…We tested the mRNA expression of CAV1 and CAVIN1 in GBM cells exposed to hyperosmotic or hypo‐osmotic medium for 48 hours (Figure A). The osmolality was adjusted by adding sodium chloride as previously described . Hyperosmolality (440 mOsmol/kg) caused a slight increase (around 2‐fold) in mRNA of CAV1 and CAVIN1 in the U251 cell line.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We tested the mRNA expression of CAV1 and CAVIN1 in GBM cells exposed to hyperosmotic or hypo‐osmotic medium for 48 hours (Figure A). The osmolality was adjusted by adding sodium chloride as previously described . Hyperosmolality (440 mOsmol/kg) caused a slight increase (around 2‐fold) in mRNA of CAV1 and CAVIN1 in the U251 cell line.…”
Section: Resultsmentioning
confidence: 99%
“…Previous work has shown that GBM respond to hydrostatic pressure by increasing matrix proteases and EMT marker expression, and caveolae have been proposed to serve mechanosensing roles. Therefore, in the following set of experiments, we assessed whether CRISPR ablation of caveola‐forming proteins CAV1 or CAVIN1 altered the pro‐invasive response of U251 cells to hydrostatic pressure, that is 30 mm Hg applied to the cells over 48 hours, as previously described . The mRNA expression of matrix proteases (Figure a,c) and EMT markers (Figure b,d) in response to increased hydrostatic pressure was significantly lower in cells lacking caveola‐forming proteins CAV1 or CAVIN1 for the majority of the genes assessed.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations